2004
DOI: 10.1002/yea.1174
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the meiotic role of the mitochondrial ribosomal proteins Mrps17 and Mrpl37 in Saccharomyces cerevisiae

Abstract: Sporulation in the yeast Saccharomyces cerevisiae is a complex and tightly regulated pathway that involves the induction of a large number of genes. We have identified MRPS17 in a cDNA library enriched for sporulation-specific genes. Homology searches show that the first one-third of Mrps17 has strong sequence similarity to bacterial S17 proteins, suggesting that Mrps17 is a potential mitochondrial ribosomal protein. This is further supported by the fact that mrps17 cells are respiratorydeficient and that a Mr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Possible extraribosomal functions have to date been found for three of the yeast mitochondrial ribosomal proteins only. Mrps17p and Mrpl37p may play a special role in yeast sporulation [33]. The mitochondrial ribosomal protein of the small subunit, yDAP-3 [34] is well conserved between yeast and human cells and besides its translational role has a distinct function in apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Possible extraribosomal functions have to date been found for three of the yeast mitochondrial ribosomal proteins only. Mrps17p and Mrpl37p may play a special role in yeast sporulation [33]. The mitochondrial ribosomal protein of the small subunit, yDAP-3 [34] is well conserved between yeast and human cells and besides its translational role has a distinct function in apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Nonsynonymous amino acid substitutions identified in Mrpl7, Hem13, and Ppa2 are predicted by mutfunc 17 to have functional impacts as they affect conserved amino acids (Supporting Information Table S3 ). Mrpl37 works as a component of the mitochondrial ribosome 77 and its Arg89Ser substitution is predicted by NetPhosYeast 15 to introduce a phosphorylation site, with Ste7 as the predicted corresponding kinase. The mechanisms through which this phosphorylation site introduction aids in acquiring ethanol tolerance remain to be tackled.…”
Section: Resultsmentioning
confidence: 99%
“…Spore formation in Saccharomyces cerevisiae is a complex and tightly regulated pathway involving the induction of a large number of genes. Hanlon et al [21] identified MRPS17 in the cDNA library of spore-specific genes. The homology search showed that the first third of Mrps17 has strong sequence similarity with the bacterial S17 protein, which indicates that Mrps17 is a mitochondrial ribosomal protein.…”
Section: Discussionmentioning
confidence: 99%